An Update on Alcoholic Steatohepatitis - Pradhan, Bickram; Arjyal, Lubina; Chaudhary, Shatdal (Journal of Universal College of Medical Sciences, 2015)
Alcoholic steato hepatitis (ASH) is an acute hepatic manifestation occurring from heavy alcohol ingestion. It is associated with liver failure, hepatorenal syndrome, severe sepsis and increased mortality. Patients with severe ASH have reported short-term mortality of up to 40%-50%. Although approximately 20% of alcoholics undergoing liver biopsy reveal histological features of alcoholic hepatites (AH) only a minority progress to severe alcoholic hepatitis (AH) with markedly elevated serum liver enzymes, jaundice and impaired liver function. Prognostic scores include the Maddrey's discriminant function, the model of end-stage liver disease, the Glasgow Alcoholic Hepatitis score, and the ABIC score. The response to corticosteroid therapy can be assessed using the Lille model. Severe ASH at risk of early death should be identified by one of the available prognostic scoring systems before considering specific therapies. Corticosteroids are the mainstay of treatment for severe ASH. When corticosteroids are contraindicated, Pentoxifylline may be alternatively used. This review article aims to discuss the clinical features, diagnosis, prognostic models, and treatment of ASH. Journal of Universal College of Medical Sciences Vol. 3, No. 1, 2015: 54-59